Fiber Forming Capability of Binary and Ternary Compositions in the Polymer System: Bacterial Cellulose-Polycaprolactone-Polylactic Acid - GÜNDÜZ, OĞUZHAN (MDPI, 2019)
Bacterial Cellulose (BC) has over recent decades shown great versatility in wound healing dressings, but is di ffi cult to spin fibers with at high concentrations. An investigation into the preparation of bandage-like fibrous meshes is carried out to determine the optimal blend of polycaprolactone (PCL) and polylactic acid (PLA) as a suitable carrier for BC. Using a simple centrifugal spinning setup, polymer blends of PCL, PLA and BC are investigated as a ternary system to determine the most suitable composition with a focus on achieving maximal BC concentration. It is found that BC content in the fibers above 10 wt % reduced product yield. By creating blends of PLA-PCL fibers, we can create a more suitable system in terms of yield and mechanical properties. The fibrous samples are examined for yield, fiber morphology using scanning electron microscopy, mechanical properties using tensile testing and chemical characteristics using Fourier-transform infrared spectroscopy. A fibrous sca ff old with > 30 wt % BC was produced with enhanced mechanical properties owing to the blending of PLA and PCL.
Keywords: polycaprolactone; polylactic acid; bacterial cellulose; polymers; fibers; MECHANICAL-PROPERTIES; NANOFIBERS; DIAMETER; NANOCELLULOSE; REGENERATION; SCAFFOLDS; MEMBRANES; GYRATION; INFUSION; PLA/PCL